The Effects of Interactive Word Walls on the Comprehension and Vocabulary Knowledge of Kindergarten Students in Reading - Karr, Morgan (My University, 2019)
The purpose of this study was to determine the impact of interactive word walls on reading comprehension and vocabulary knowledge of kindergarten students. The participants in this study consisted of nineteen kindergarten students enrolled at an elementary school in Harford County, Maryland. The participants were provided with interactive word wall instruction and practice aligned with the Common Core State Standards in reading as well as the local school system’s English Language Arts curriculum. The Fountas and Pinnell Benchmark Assessment was utilized to compare the scores of students before and after receiving word wall instruction. The analysis of data revealed the interventions had a positive impact on students’ comprehension and vocabulary knowledge.
Keywords: Interactive Word Walls; Kindergarten; Education -- Research papers (Graduate).